Analisis kemampuan konseptual dan implementasi TPACK guru profesional matematika (tersertifikasi) di SMPN se-kota mataram - Kurniawan, Eka; Gilang Primajati; M. Ginawan Supiarmo; Dita Oktavihari; Musaddad, Aras Maulana (Mandalika Mathematics and Educations Journal, 2025)
This study aims to analyze the ability and implementation of TPACK of professional SMPN teachers in the city of Mataram. Data collection techniques use questionnaires, interviews, and documentation. The questionnaire referred to in this study is a questionnaire to measure the teacher's TPACK ability, then for interviews to find out the obstacles or results of the implementation of TPACK-based learning. And the documentation referred to in this study is a set of TPACK-based learning ranks with the hope of providing an overview related to the planning, implementation and evaluation of the implementation of TPACK-based learning. The results of this study can be concluded that the conceptual ability and implementation of TPACK of professional (certified) teachers in Mataram City are able to support the 21st century skills of students. The results of the analysis of the questionnaire showed that KINDERGARTEN, PK, PTK, PVK, and TPACK said high while CK and TCK said medium grade. Likewise, with its implementation, the average mathematics teacher can integrate technology into PPT and LKPD. For example, by using learning videos from youtube, quizizz, canva, kahoot, etc. Some of the equipment that supports the TPACK-integrated learning process include laptops, LCDs, projectors, Wifi, Speakers, smartphones, etc. Then some of the obstacles faced by teachers when implementing TPACK-integrated learning include a lack of device units, unstable wifi, low student interest and motivation